Effects of different particle size of rapeseed and linseed in fattening lamb diets. I. Growth and slaughter performance - Borys B.; Jarzynowska A.; Janicki B.; Borys A. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The effects of intensively feeding fattened lambs to 30-35 kg body weight with rapeseed and linseed (10% of the diet, 2:1 ratio) and of the form of these (whole, or 50 or 100% ground) on fattening performance and slaughter value were investigated. Lamb growth, feed intake and feed conversion were not affected by the proportion or form of oilseeds. The use of ground oilseeds had a beneficial effect on the EUROP carcass score, with increased external fatness, a tendency towards greater slaughter yield and loin eye area, and no differences in the leg tissue composition. Crossing prolific sheep with Texel rams did not result in differences in the lamb growth rate and had a beneficial effect on live and post-mortem evaluation of meatiness, with lower carcass fatness and no differences in the leg tissue composition. The overall effect of using rapeseed and linseed in all-mash for lambs fattened to high weight standards is initially considered as beneficial in terms of fattening results and the slaughter value of the lambs. The best effects can be expected when using partly ground oilseeds.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)